PERAN GURU SEBAGAI MOTIVATOR DALAM MENINGKATKAN KECERDASAN SPIRITUAL SISWA DI MTS NURUL IMAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Tuti Alawiyah, Siti Shavira Ananda. (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
The research in this thesis is motivated by a phenomenon that spiritual intelligence has not been paid much attention to by educators and parents because it prioritizes learning achievement in the form of good report cards or only intellectually. In addition to informal education from the family, formal education by educators or teachers also has a role in increasing students' spiritual intelligence. As a PAI teacher who has a role as a motivator, it is expected to increase students' spiritual intelligence. This study aims to determine the role of the teacher as a motivator in increasing spiritual intelligence, spiritual intelligence, and the influence of the teacher's role as a motivator to increase the spiritual intelligence of students at MTs Nurul Iman Tanjung Morawa, Deli Serdang Regency. The population in this study were all 230 students at MTs Nurul Iman Tanjung Morawa. From the population set a sample of 20% of the population, namely 46 students using random sampling technique. Research data were collected through questionnaires and analyzed using descriptive and correlational analysis techniques using the r Product Moment Correlation formula. Based on the results of data analysis, it was found that: The teacher's role as a motivator in improving the spiritual intelligence of MTs Nurul Iman Tanjung Morawa students, Deli Serdang Regency belongs to category A (very good) with an average value of 80.13. The spiritual intelligence of MTs Nurul Iman Tanjung Morawa students, Deli Serdang Regency, belongs to category A (very good) with an average score of 80.60. The influence of the teacher's role as a motivator on increasing the spiritual intelligence of MTs Nurul Iman Tanjung Morawa students, Deli Serdang Regency, based on the results of the correlation test, was significant at the 95% confidence level, obtained rxy rtable (0.959 0.291) categorized as high relationship. This means that the influence of the teacher's role as a motivator to increase the spiritual intelligence of students at MTs Nurul Iman Tanjung Morawa, Deli Serdang Regency, is 92% and shows that only 8% of students' spiritual intelligence is influenced by other factors.